BENTUK PERLINDUNGAN TERHADAP ANAK YANG MENJADI KORBAN KEJAHATAN SEKSUAL SESAMA JENIS (STUDI KASUS DINAS PENGENDALIAN PENDUDUK KELUARGA BERENCANA PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN ROKAN HILIR) - Syahputra, Dandy; Widya Ramailis, Neri (SISI LAIN REALITA, 2022)
In essence, children are the next generation of the nation, so treating children well is our collective obligation, so that children can grow and develop well. This study discusses the form of protection for children who are victims of same-sex sexual crimes in Rokan Hilir Regency which are handled by the DP2KBP3A service. The method used in this study is a qualitative method with a descriptive type of research by conducting interviews with key informants and informants. in this study include the Head of the DP2KBP3A Service, Child Protection Division, Advocacy Section for Child Information Facilities, Community Leaders, Victims, Victims' Families, using data obtained by researchers which are then associated with criminological theory showing that the form of protection from DP2KBP3A Rokan Hilir district in handling cases of same-sex sexual crimes against children, starting with reporting, then outreach to victims, case management, temporary shelter in safe houses, then mediation, assisting victims and conducting outreach activities in sub-districts and villages in the district n Rokan Downstream.